Histologic findings and viral antigen distribution in natural coinfection of layer hens with subgroup J avian leukosis virus, Marek's disease virus, and reticuloendotheliosis virus. (September 2019) - Liu, Hongmei; Ma, Kui; Liu, Miaomiao; Yang, Chengcheng; Huang, Xueting; Zhao, Yu; Qi, Kezong
We investigated the histologic findings and viral antigen distribution in 3 cases of natural coinfection of layer hens with subgroup J avian leukosis virus (ALV-J), Marek's disease virus (MDV), and reticuloendotheliosis virus (REV) in hens. At autopsy, diseased hens were found to have hepatosplenomegaly and thickened proventriculi, with white tumor nodules in the liver, spleen, lung, kidney, and ovary. Microscopically, most tissues had been infiltrated by neoplastic lymphocytes; the spleen, lung, proventriculus, heart, and liver had been infiltrated by both neoplastic lymphocytes and myeloblastic cells and/or primitive reticular cells. Fluorescence multiplex immunohistochemistry staining revealed ALV-J, MDV, and REV antigens co-expressed in the same tissue, even the same cell.